Nanoparticle Tension Probes Patterned at the Nanoscale: Impact of Integrin Clustering on Force Transmission - Liu, Yang (American Chemical Society, 2014)
[Image: see text] Herein we aimed to understand how nanoscale clustering of RGD ligands alters the mechano-regulation of their integrin receptors. We combined molecular tension fluorescence microscopy with block copolymer micelle nanolithography to fabricate substrates with arrays of precisely spaced probes that can generate a 10-fold fluorescence response to pN-forces. We found that the mechanism of sensing ligand spacing is force-mediated. This strategy is broadly applicable to investigating receptor clustering and its role in mechanotransduction pathways.